Clinical, radiographic and biochemical assessment of proximal cavities restored with composite resin using incremental vs. bulk packing techniques: One-year randomized clinical trial - Monaliza Maher Abdelaziz; Shereen Fathy; Amany Ahmed Alaraby; Wessam Ibrahim Shehab; Marwa Mohamed Temirek (BMC, 2024)
Abstract Background Bulk-fill resin composites may suffer from recurrent caries around compound proximal restorations in posterior teeth, especially at the proximo-gingival interface.Over 12 months, will the bulk fill technique affect the caries recurrence rate at gingival margins when compared to the conventional incremental packing technique? How early will the first clinical, radiographical, and biochemical evidence of caries recurrence occur? Methods After randomization, in 30 patients with two compound (OM or OD) supragingival lesions, one tooth was restored using the bulk fill technique on one side (group 1) (n = 15). In contrast, the other tooth on the other side was restored utilizing the incremental layering technique (group 2) (n = 15). Both teeth received restorative material (X-tra fil, Voco, Cuxhaven, Germany). The FDI criteria were used to evaluate restorations. As for the periodontal assessment, the gingival index, plaque index, papillary bleeding scoring index and periodontal pocket depth were evaluated. The gingival crevicular fluid (GCF) specimens were gathered, and MMP-9 was extracted and quantitated by ELISA. A customized radiographic template was designed, and 3D printed digital bitewing radiographs were taken. Assessments were done clinically, radiographically and biochemically at baseline (1 week) and after 3, 6 and 12 months. Data was statistically analyzed. Results The null hypothesis was accepted clinically; no statistically significant differences appeared between bulk and incrementally filled posterior restorations. As for the radiographic assessment, the null hypothesis was accepted except for increased periodontal ligament width at 3 months. The null hypothesis for the biochemical evaluation was rejected as there were significant changes in levels of MMP-9 at different testing times. Conclusions 1. With similar results but less sensitivity and significant time saving, the bulk fill technique can be considered an efficient alternative to the incremental fill technique in restoring proximal cavities. 2. Early evidence of caries recurrence can be correlated to an increase in the MMP-9 level in gingival crevicular fluid, followed by an increase in radiographic periodontal ligament width measurement. Trial registration An ethical approval from the Research Ethics Committee at the Faculty of Dentistry, October 6 University, (Approval No. RECO6U/5-2022). The study was registered at the Pan African Clinical Trials Registry on 24/07/2023 with an identification number (PACTR202307573531455).